PERENCANAAN LANSKAP KAWASAN WISATA BERKELANJUTAN DI KECAMATAN CISARUA, KABUPATEN BOGOR - Adriani, Hanni; Hadi, Setia; Nurisjah, Siti (http://arl-faperta.ipb.ac.id/, 2016)
Indonesia is a tropical country, has various natural resources and social resources. Because of that Indonesia has many place as destination for recreation and tourism areas, but various positive and negative impact happened from that. This study aims to identify and analyze the landscape visual quality, the public acceptability of the development of tourism, tourist characteristics and preferences, and planning tourism zone of the mountains for the development of the tourism area. Case studies conducted in Cisarua sub-district which is part of the Puncak mountainous tourist area is very well known in West Java, with an area of 66.72 km2. Data obtained from field observation, published data, government reports and interviews with local residents, and tourists who visit the area. Data were statistically analyzed qualitatively and quantitatively by using a scoring method based assessment criteria, Geographic Information System (GIS) and SBE method (Scenic Beauty Estimation). The results showed that local communities can receive tourism development because it has increased their revenues from tourism. Tourism have been shifted their livelihood from agriculture to tourism. The tourists, they are less comfortable with the current state of overcrowding by vehicles, less clean and less comfortable, as well as the occurrence of significant changes in mountain view. To maintain the sustainability of the environment, the development must be carried out in areas that have a high potential tourism zone. Besides protecting the environment, also positive economic impact for the local community can continue and increase demand, so sustainable tourism concept needs to be done in this area.